Competitive strategies of late followers in auto industry: case study Hyundai-Kia - Rakita, Branko; Madić, Vladan; Marković, Dušan (Industrija, 2017)
This paper analyzes competitive strategy of late followers in auto industry in the case of Hyundai Kia Auto Group (HKAG). The global economic crisis has had a strong impact on the leaders in auto industry. HKAG took advantage of the crisis and increased sales and global market share at the expense of the leaders in the industry. We found that during the crisis the company achieved excellent results thanks to innovative marketing and sales strategies combined with top quality, product design and productivity. Growing competition and changes in business environment in the post-crisis period jeopardized the future growth of the company. The company reacted to the changes in business environment by shifting the focus to the luxury segment and green vehicles, by launching independent luxury brand Genesis and by scaling up investment in R&D.